THE PLACE OF THE SPIRITUAL HERITAGE OF ABU ISA TERMIZI IN THE DEVELOPMENT OF ISLAMIC SCIENCE (TAMADDUN NURI JURNALI, 2024)
The scientific and spiritual heritage of Abu Isa Termizi, the exemplary life path of the scientist is covered in the article based on historical and philosophical sources. Also, scientific analyzes are presented on the scholar's muhaddith activities and his place in the development of the science of hadith.